ALGORITMA LABELING CITRA BINER DENGAN PERFORMANSI OPTIMAL PROCESSOR-TIME - Mozef, Eril (Institute of Research and Community Outreach - Petra Christian University, 2004)
In the literature, some labeling algorithms of nxn binary image, which are generally claimed as optimal, are only optimal with regards to the algorithmic aspect but not to the architectural aspect. Aside from this, the complexities obtained are not pure because the constant still depends on the value of n. This paper presents a labeling algorithm, which reaches purely Processor-Time optimal performance. This means that the optimal performance is not only reached considering its algorithm but also its architecture and